Rhabdomyolysis following snapper fish consumption (Haff disease): a family affair. Issue 6 (14th June 2022) - Das, Adarsh; Khoo, Timothy; England, Thomas; Lim, Wai Hon
Abstract : This case describes the first report of Haff disease in Australia, where a family of three all presented with myalgia, after ingesting recently thawed, baked queen snapper fish, caught off the coast of Western Australia. All three members (mother, father and son) developed rhabdomyolysis; however, the son, who had a higher creatine kinase level, also developed an acute kidney injury, likely linked to his double fish consumption. All members were admitted for intravenous hydration and clinically improved. This case highlights the importance of dietary and environmental history in cases of rhabdomyolysis without an obvious aetiology in an otherwise self-limiting disease.